As relações entre as merendeiras e as crianças em uma Unidade Municipal de Educação Infantil de Belo Horizonte: "cuidar, ensinar, zelar, educar, tudo faz parte das nossas responsabilidades!" - Bárbara Souza Teixeira (2018)
This research aimed to understand how the interactions between lunch ladies and children occur in a Municipal Unit of Early Childhood Education (UMEI) of Belo Horizonte. The theoretical framework used has articulated studies of Early Childhood Education, Sociology of Childhood and Historical-Cultural Psychology, , From the theoretical-methodological point of view, a qualitative research was developed, which had as instruments the observation with record in field diary and semi-structured interviews. The observations and interviews revealed coincidences among other studies that have lunch ladies as subjects. Their profile is mainly composed by women, who are poor and black. They perform a heavy, low-paid, and often invisible task. The cooking labor that they perform remunerably has been learned by them since childhood in various situations of life. The training they receive is scarce and generally, in this training, their activity is reduced to food handling. However, the research results have shown that, although meal times are tumultuous, children and lunch ladies relate to each other and create bonds. In general, they demonstrate that they are aware of their importance in the education and care of children, and we consider that part of this awareness refers to an active presence of the institution's management in an effort to guide them to maintain respectful actions towards the children.